A Four-Dimensional Analysis of Organizational Complexity among (SMEs)(SMEs) Entrepreneurs with Registered Capital of 10 Million Baht and Above - อินเสือ อังคณา; ภู่สกุล ปภัชญา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
SME entrepreneurs with registered capital of 10 million baht and above constitute a vital segment driving Thailand’s economic development through employment creation, tax revenue, and supply chain stability. As these businesses expand, they encounter heightened organizational complexity across four dimensions: organizational structure, accounting and information systems, financial and tax compliance, and corporate governance. Such complexity is further intensified by insufficiently skilled personnel, fragmented data environments, and regulatory frameworks that are difficult to interpret (OSMEP, 2023; IFAC, 2022). This study employs a qualitative research methodology utilizing three research instruments: (1) Systematic Literature Review drawing on academic sources and national and international organizational reports; (2) Content Analysis to categorize dimensions of systemic complexity; and (3) Comparative Analysis between lower-capital and higher-capital SMEs to identify structural differences. The theoretical framework integrates four contemporary theories: Organizational Complexity Theory, Digital Accounting Information Systems Theory, the COSO ERM Framework (2017), and Contemporary Corporate Governance Theory. The findings reveal that SMEs in this capital tier face elevated risks in data accuracy, accounting errors, cost mismanagement, and governance deficiencies as they transition toward professionalized management. Improving accounting information systems, adopting the COSO ERM framework, strengthening employee competencies, and implementing sound governance practices are identified as critical strategies for reducing organizational complexity and fostering sustainable growth among SMEs in this segment.